The Relationship between the History of Exclusive Breastfeeding and Complementary Feeding (MP-ASI) with Stunting among Children Under Five in the Working Area of Penana'e Public Health Center, Bima City: A Cross-Sectional Study - Agnis Setiawati; M. Noris; Darmin; Juraidin (Jurnal Kesehatan Komunitas Indonesia, 2026)
Background: Stunting is a chronic nutritional problem that remains a public health challenge in Indonesia, including in the working area of the Penana'e Health Center in Bima City. Inappropriate practices of exclusive breastfeeding and complementary feeding can affect toddler growth and increase the risk of stunting. Objective: This study aims to determine the prevalence of stunting and to analyze the relationship between the history of exclusive breastfeeding and complementary feeding and stunting in the working area of the Penana'e Health Center in Bima City. Methods: A cross-sectional study was conducted in the working area of Penana'e Primary Health Center, Bima City, Indonesia. A total of 80 mothers with children aged 6–59 months were included. The sample size was determined using the Slovin formula, and participants were selected using purposive sampling based on predetermined inclusion and exclusion criteria. Data were collected through structured interviews using a validated questionnaire. Data were analyzed using descriptive statistics and Pearson's Chi-square test. Effect sizes were expressed as Odds Ratios (ORs) with 95% Confidence Intervals (95% CIs). Results: Exclusive breastfeeding was significantly associated with stunting (p<0.001). Children who were not exclusively breastfed had 4.96 times higher odds of being stunted than those who received exclusive breastfeeding (OR=4.96; 95% CI=1.86–13.23). In addition, the timing of complementary feeding was significantly associated with stunting (p<0.001). Children who received complementary feeding either before or after six months of age had 5.32 times higher odds of stunting than those who received complementary feeding at six months (OR=5.32; 95% CI=1.97–14.32). Conclusion: The history of exclusive breastfeeding and MP-ASI is related to the incidence of stunting in toddlers in the working area of the Penana'e Health Center, Bima City, so it is necessary to increase education to mothers about the importance of providing exclusive breastfeeding and appropriate MP-ASI to prevent stunting.